1995
DOI: 10.1111/j.1464-5491.1995.tb02061.x
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and Free Radical Activity in Young Adults with Insulin‐dependent Diabetes

Abstract: Cigarette smoke is potentially capable of generating a high free radical load in the body and many patients with diabetes are smokers. This study was designed to investigate the relationship between long-term smoking and free radical activity in young adult insulin-dependent diabetic patients with no evidence of macrovascular disease. Eight-five patients (48 male) aged 17-40 years were studied. Mean duration of diabetes was 10.5 years (0.08-33) and 39 were cigarette smokers. All had normal serum creatinine lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Cigarette smoking has been associated with increased oxidation of RBCs and plasma although it seems that, at least, in young smokers it also activates the RBCs antioxidant mechanisms as an adaptation process to counteract the oxidant factors [40], [41]. Our findings by documenting a relatively small increase (∼20%) in the PCI and ROS accumulation in RBCs from middle aged smokers corroborate these previous reports.…”
Section: Discussionsupporting
confidence: 89%
“…Cigarette smoking has been associated with increased oxidation of RBCs and plasma although it seems that, at least, in young smokers it also activates the RBCs antioxidant mechanisms as an adaptation process to counteract the oxidant factors [40], [41]. Our findings by documenting a relatively small increase (∼20%) in the PCI and ROS accumulation in RBCs from middle aged smokers corroborate these previous reports.…”
Section: Discussionsupporting
confidence: 89%
“…Investigations into the degree of lipid peroxidation in smokers of nonuremic populations have yielded inconsistent results [23, 24, 25]. These differences are probably due to differences in the assays used to measure lipid peroxidation [26].…”
Section: Discussionmentioning
confidence: 99%
“…Both unchanged and diminished Cu,Zn-superoxide dismutase activity in erythrocytes of diabetic patients have been reported and there are conflicting results regarding the influence of glycaemic control on dismutase activity (7)(8)(9). It was clearly demonstrated that erythrocyte su-! )…”
Section: Introductionmentioning
confidence: 99%